Data from: Gain-of-function experiments in bacteriophage lambda uncover residues under diversifying selection in nature - Maddamsetti, Rohan; Johnson, Daniel T.; Spielman, Stephanie J.; Petrie, Katherine L.; Marks, Debora S.; Meyer, Justin R. (Dryad, 2018)
Viral gain-of-function mutations frequently evolve during laboratory
experiments. Whether the specific mutations that evolve in the lab also
evolve in nature and whether they have the same impact on evolution in the
real world is unknown. We studied a model virus, bacteriophage λ, that
repeatedly evolves to exploit a new host receptor under typical laboratory
conditions. Here we demonstrate that two residues of λ’s J protein are
required for the new function. In natural λ variants, these amino acid
sites are highly diverse and evolve at high rates. Insertions and
deletions at these locations are associated with phylogenetic patterns
indicative of ecological diversification. Our results show that viral
evolution in the laboratory mirrors that in nature and that laboratory
experiments can be coupled with protein sequence analyses to identify the
causes of viral evolution in the real world. Furthermore, our results
provide evidence for widespread host-shift evolution in lambdoid viruses.
DRYAD-J-alignment-Evolution
Keywords: Host Shift; Synthetic biology; Gain-of-Function; Genomic Epidemiology; Natural Variation